اختيارات ابن العثيمين الأصولية في باب الحكم الشرعي - شارف, بلال; سحنون, طارق; حوامدي, موسى الأحمدي (جامعة الوادي - University of Eloued, 2019)
يدرس هذا البحث اختيا ا رت ابن عثيمين الأصولية في باب الحكم الشرعي والهدف منه هو التعرف عن آ ا رء وأقوال الشيخ في مسائل الحكم الشرعي الأصولية وذلك من خلال عرض المسائل الأصولية المتعلقة بالحكم الشرعي بعد جمعها من كتب أصول الفقه ثم ذكر اختيار الشيخ بن عثيمين في هذه المسائل بعد استق ا رء كتبه وتتبع أقوله في هذه المسائل. فخلصنا في آخر البحث إلى أن الشيخ بن عثيمين من أهل الاختيار في آ ا رءه الأصولية لأنه لم يتقيد بمذهبه بل اتبع الدليل في ترجيحاته الأصولية Abstract This study deals with the choices of Ibn uthaymeen fundamentalism in the section of the islamic ruling.the purpose of this is to identify the views and sayings of the Shaykh in matters of islamic fundamentalism by presenting the fundamental issues related to the islamic ruling after collecting them from the books of the fundamentals of fiqh.then he mentioned the selection of Shaikh Ibn uthaymeen in these matters after extrapolation he wrote and followed his words in these matters.we concluded in the lastn resarch that Shaikh ibn uthaymeen of the people of choice in his fundamentalist viwes becoause he did not adthere to his doctrine,but follow the evidence in his fundamentalist statements
مذكرة ليسانس
Keywords: اختيارات /ابن العثيمين /الحكم الشرعي; Options / Ibn Al-Options / Ibn Al-Uthaymine / Décision de la charia / Décision de la charia